The effect of breast stimulation on the duration of labor stages: A systematic review and meta-analysismeta-analysis - Mojgan Mirghafourvand; Mahsa Maghalian; Robab Hassanzadeh (Mashhad University of Medical Sciences, 2024)
Introduction: Prolonged labor stages can have serious consequences for both mother and infant. Positive effects and encouraging results of nipple stimulation on the duration of labor have been observed in some studies. This study was performed with aim to determine the effects of breast stimulation on the duration of labor (primary outcome) and Apgar score and method of delivery (secondary outcomes). Methods: This systematic review and meta-analysis was conducted according to the PRISMA guidelines. A search of published Persian and English texts without time restrictions up to July 2023 was performed in reputable databases including Scopus, Web of Science, Google Scholar, PubMed, and the SID Persian database with English keywords of Stimulation, Physical stimulation, Labor progress, Labor stage, Duration of labor, Breast, Nipple, and Labor, as well as their equivalent Persian keywords. Two authors independently assessed the quality of the articles using the Cochrane Risk of Bias tool and ROBINS-I tool, and the meta-analysis was conducted using RevMan software (version 5.3). Results: Out of 307 identified studies, 10 articles met the inclusion criteria. According to the subgroup analysis based on the control group, nipple stimulation compared to no intervention significantly reduced the duration of the first stage of labor (4 studies, mean difference: -2.66; 95% confidence interval: -1.70 to -3.61; p<0.001) and the second stage of labor (3 studies, mean difference: -8.22; 95% confidence interval: -3.62 to -12.83; p<0.001). Conclusion: Although breast stimulation compared to no intervention may reduce the duration of labor, due to the limited studies in this area, further high-quality studies are needed before recommending its use.